2021
DOI: 10.1182/blood-2021-146518
|View full text |Cite
|
Sign up to set email alerts
|

Updated Clinical and Correlative Results from the Phase I CRB-402 Study of the BCMA-Targeted CAR T Cell Therapy bb21217 in Patients with Relapsed and Refractory Multiple Myeloma

Abstract: Introduction: Idecabtagene vicleucel (ide-cel, bb2121) is the first chimeric antigen receptor (CAR) T cell therapy approved for the treatment of relapsed or refractory multiple myeloma after four or more prior lines of therapy, including an immunomodulatory agent, a proteasome inhibitor, and an anti-CD38 monoclonal antibody. bb21217 is a B-cell maturation antigen (BCMA) directed CAR T cell therapy which uses the same CAR molecule as ide-cel, with the addition of a PI3K inhibitor (bb007) during ex vivo culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…The preliminary results of its preclinical study have been reported before, and the subsequent results presented in ASH2021 showed that adding PI3K inhibitor (BB007) during the in vitro culture stage to amplify memory-like T cells (CD62L + and CD27 + ) ( 74 , 75 ) could advance the persistence of CAR-T cells literally. This positive effect was reflected on a better DOR of bb21217 compared with bb2121 ( 65 ), which shared the same CAR structure with it ( 55 ). Moreover, after infusing bb21217, CAR-T cells could be detected in 30/37 (81%) patients and 9/15 (60%) patients at 6th and 12th months.…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary results of its preclinical study have been reported before, and the subsequent results presented in ASH2021 showed that adding PI3K inhibitor (BB007) during the in vitro culture stage to amplify memory-like T cells (CD62L + and CD27 + ) ( 74 , 75 ) could advance the persistence of CAR-T cells literally. This positive effect was reflected on a better DOR of bb21217 compared with bb2121 ( 65 ), which shared the same CAR structure with it ( 55 ). Moreover, after infusing bb21217, CAR-T cells could be detected in 30/37 (81%) patients and 9/15 (60%) patients at 6th and 12th months.…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 99%
“…Moreover, the preliminary results of many other related studies, such as the engineering improvement strategies to existing CAR-T-cell products or the effects induced by multiple factors inside and outside the body, were reported in this meeting. The relevant data about the safety and efficacy of those products, including ciltacabtagene autoleucel (cilta-cel) ( 46 48 ), CT053 ( 49 , 50 ), CT103A ( 51 ), C-CAR088 ( 52 ), PHE885 ( 53 ), CART-ddBCMA ( 54 ), and bb21217 ( 55 ), are presented in Table 2 , and the relevant supplementary explanations will be carried out later in this paper.…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 99%
“…This approach is being evaluated with the bb21217 anti‐BCMA product, which involves the use of ex vivo culture of the cells with a phosphoinositide 3‐kinase inhibitor. Preliminary results from the ongoing phase I study of this product suggest that patients with higher than median number of CD8+ CAR T‐cells expressing CD27/CD28 had significantly longer duration of response compared to patients with lower than median values ( P = 0.0024) 20 …”
Section: Figurementioning
confidence: 99%
“…Preliminary results from the ongoing phase I study of this product suggest that patients with higher than median number of CD8+ CAR T-cells expressing CD27/ CD28 had significantly longer duration of response compared to patients with lower than median values (P = 0.0024). 20 As CAR T-cells represent a therapy that can replicate and sustain itself over time, an improved understanding of mechanisms driving in vivo CAR T-cell expansion and persistence is needed. There has been much scrutiny over whether therapies administered to manage CAR T-cell-induced CRS can abrogate expansion and efficacy.…”
Section: Quantitative Clinical Pharmacology Of Car T-cell Therapymentioning
confidence: 99%
“…An updated version of the ide-cel product, bb21217, has also been evaluated in early phase trials. Unlike ide-cel, bb21217 is cocultured with a PI3K inhibitor to increase the number of memory-like T cells and remove senescent cells from the CAR T product (96). So far, an ORR of 69% has been observed in a phase 1 trial.…”
Section: Car T Cellsmentioning
confidence: 99%